Pemanfaatan Media Pembelajaran Bahasa Arab Berbasis Artificial Intelligence Melalui Aplikasi Canva - Nurhasanah, Siti; Dede Pahrudin (Ta'bir Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Ilmu Kebahasaaraban, 2025)
This research explores the use of Artificial Intelligence (AI) based Arabic language learning media through the Canva application. This research aims to analyze the importance of media in learning and also the use of ArtificiaI Intelligence (AI) based media in the Canva application. This type of research is qualitative with observation, interview and documentation methods. The object of this research was carried out at Madrasah Tsanawiyah Harapan Baru. Data analysis techniques using data collection, data reduction, data presentation, and drawing conclusions. There are several things that can be concluded from this research, namely: 1) The Importance of Media in Learning: Media plays an important role in learning, with the aim of not only conveying information but also making learning more interesting and enjoyable. 2) The use of Artificial Intelligence (AI) based media in the Canva application has a big impact when creating learning media that makes learning activities more interesting, interactive and develops better learning strategies.